The Study On The Interrelation Of Magnetism And Superconductivity In Smfe (O1-Xfx) As Compounds - Endris Yimam (My University, 2017)
This work focuses on the study of interrelation of superconductivity and magnetism in SmFeAsO1-xFx. Starting with a reasonable Hamiltonian and using Green functions formalism, we have obtained expressions for Tc, Tm and superconductivity and magnetic order parameters and respectively. For suitable value of the parameters the phase diagram is obtained which shows the possibility of the interrelation of superconductivity and magnetism in SmFeAsO1-xFx .